Sintered Carbide Materials
Patent Information
- Application Number
- JP2023568001
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-05-03
- Filing Date
- 2022-04-21
- Publication Date
- 2025-04-28
AI Technical Summary
The existing cemented carbide has a wear and loss of bonding agent due to the decrease in the strength of the metal bonding agent under high temperature conditions, which affects the retention of hard tungsten carbide grains and is insufficient in wear resistance.
A cemented carbide containing 70-95% by weight of dispersed tungsten carbide and a binder phase is used, and 1-28% by weight of metal bonding material and 1-28% by weight of intermetallic phase material are added to the binder to form an intermetallic phase material with (M,Y)3 (Al,X) structure to enhance the strength of the bonding phase.
It significantly improves the wear resistance and fracture strength of cemented carbide, especially maintains good mechanical properties under high temperature conditions, and is suitable for high-load environments such as earth excavation tools.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a cemented carbide material, in particular a hard alloy, comprising 70-95% by weight of tungsten carbide in dispersed form and a binder phase, the binder phase comprising a metallic binder material, in particular Co.
[0002] EP 2 691 198 describes such a cemented carbide material, i.e. a hard alloy body, and a method for its production. According to this known method, a powder containing coarse-grained tungsten carbide and a larger than stoichiometric proportion of carbon and cobalt powder is mixed. Powdered tungsten is then added to this powder. The tungsten powder and the cobalt powder had an average grain size of about 1 μm. The coarse-grained tungsten carbide had an average grain size of 40.8 μm.
[0003] The powder was then ground in a ball mill, to which hexane and paraffin wax were added. A green compact was produced from the mixture by pressing, and the green compact was then sintered. After the sintering process, the resulting sintered carbide material was subjected to a heat treatment, where it was heated to 600°C and held at this temperature for 10 hours.
[0004] After a subsequent cooling step, the sintered carbide material was subjected to analysis, where it was found to have nanoparticles in the binder phase, the nanoparticles having a size of less than 10 nm. The nanoparticles were formed by eta phase (Co3W3C) or (Co6W6C) or theta phase (Co2W4C). The grain size of the nanoparticles was less than 10 nm.
[0005] It turns out that nanoparticles are accompanied by a strengthening of the binder phase, which allows for an increase in the hardness of cemented carbide materials. The drawback of these materials is the lack of thermal stability of the nanoparticles, which makes them only suitable to a limited extent for high temperature applications or those where high temperature inputs occur.
[0006] During rock processing and cutting of asphalt and concrete, friction generates very high temperatures on the tool surface. The hard material tungsten carbide is not significantly affected by these temperatures, as it has a high hot hardness even at these temperatures. However, the strength of the metal binder decreases dramatically at these temperatures. When the strength of the metal binder decreases, the stresses of use result in increased wear and tear and dissolution of the binding phase. As a result, the tungsten carbide grains can no longer be held in the hard alloy.
[0007] It is an object of the present invention to provide a cemented carbide material, in particular a hard alloy, which has improved wear resistance and at the same time high fracture strength.
[0008] This problem is solved by the invention with the features of claim 1. Thereby, a sintered carbide material, in particular a hard alloy, is proposed which comprises 70-95% by weight of tungsten carbide in dispersed form and a binder phase, which comprises a metallic binder material and at least in partial regions of the sintered carbide material also comprises an intermetallic phase material, the proportion of the metallic binder material in the sintered carbide material being 1-28% by weight, the proportion of the intermetallic phase material in the sintered carbide material being 1-28% by weight, the metallic binder material comprising Co, the intermetallic phase material being formed according to the structural formula (M,Y)3(Al,X), where M=Ni, Y=Co and / or other components and X=tungsten and / or other components.
[0009] Therefore, according to the invention, a cemented carbide material, in particular a hard alloy, is proposed which comprises a strengthening binder phase, the strengthening of which is caused by intermetallic phase materials which form crystalline intercalations in the metallic binder.
[0010] This intermetallic phase material has significantly higher strength than the metallic binder material it is intercalated in. At the surface of the cemented carbide material subjected to abrasive attack, the intermetallic phase material reduces erosion and dissolution of the metallic binder material when used, for example, in earth-excavating tools.
[0011] The movement of the earth-digging tool and the loosened and remaining soil materials cause abrasive and mechanical loads on the cemented carbide material. The tungsten carbide grains are then sufficiently resistant to this abrasive attack. The problem here is that the strength of the binder material is significantly lower than that of tungsten carbide. Now, due to the incorporation of intermetallic phase material in the binding phase according to the invention, rapid erosion and dissolution of the metallic binder material is prevented.
[0012] Moreover, it has surprisingly been found that the intermetallic phase material also strengthens the internal structure of the cemented carbide material. In the event of strong shock-like stresses, the crystals of the intermetallic phase material reduce or prevent the sliding of the tungsten carbide particles in the region of the binder phase connecting the tungsten carbide particles and thus excessive plastic deformation of the binder phase. In particular, in this case, the individual crystals of the intermetallic phase material support one another. This is of great advantage, in particular, at high tool operating temperatures, because at these temperatures the strength of the cobalt in the binder phase is reduced, but the intermetallic phase material still ensures that it provides sufficient support for the binder material.
[0013] Overall, it has been found that the solution according to the invention allows a significant increase in the wear resistance of cemented carbide materials to be achieved. For example, tests have shown that the use of the cemented carbide material according to the invention in the form of cutting tips in round shank chisels for road milling machines increases the wear resistance by up to 50%. It has been found that such a significant increase in wear resistance can be achieved when milling asphalt and concrete road surfaces.
[0014] The sintered carbide material according to the invention can in particular be used to construct the working area of tools for the treatment, loosening, transport and processing of plant, mineral or building materials, in particular in the fields of agriculture, forestry or road construction, mining or tunnel construction.
[0015] According to the invention, the proportion of the metallic binder material in the cemented carbide material is 1-28% by weight, preferably 1-19% by weight, whereby the metallic binder material, apart from unavoidable impurities, can be entirely or almost entirely formed of Co.
[0016] It is also conceivable that, apart from unavoidable impurities, the binder material contains other elements besides Co, in particular dissolved W, C, Ni, Al and / or Fe.
[0017] In accordance with the present invention, the intermetallic phase material is formed according to the structural formula (M,Y)(Al,X), where M=Ni, Y=Co and / or other elements, and X=Tungsten and / or other elements.
[0018] Advantageously, Y=Co and X=W, at least in the majority of the crystals of the intermetallic phase material.
[0019] Furthermore, for some or all of the crystal lattice (Al,X), X can be present not only in the form of W, but also in the form of Mo and / or Nb and / or Ti and / or Ta and / or Cr and / or V.
[0020] According to the invention it is possible to provide that the binder phase comprises two or more intermetallic phase materials or only a single intermetallic phase material.
[0021] Even if more than one phase material is present, the total proportion of all intermetallic phase materials is, according to the invention, between 1 and 28% by weight in the cemented carbide material.
[0022] The cemented carbide material according to the invention can be characterized in that the proportion of intermetallic phase material in the binder phase is in the range of 25% to 70% by weight, advantageously in the range of 30% to 70% by weight, even more advantageously in the range of 35% to 60% by weight, particularly preferably in the range of 40% to 50% by weight.
[0023] In other words, for example, if the proportion of intermetallic phase material in the binder phase is in the range of 30 wt% to 70 wt%, the remaining proportion of the binder phase in the range of 70 wt% to 30 wt% may be formed by metallic binder material, which may include Co and optionally other components in accordance with the above.
[0024] When the proportion of intermetallic phase material is in the range of 30% to 70% by weight, a cemented carbide material is formed which can be used in a wide range of applications for wear protection of components. For example, wear protection applications can be realized in which the cemented carbide material is used for wear protection of surfaces, such as screen supports of high performance screens in oil sands processing. Applications according to the invention are also conceivable in which the surface of an earth-digging tool is at least partially coated with the cemented carbide material.
[0025] The sintered carbide material according to the invention can also be characterized in that the proportion of intermetallic phase material in the binder phase is in the range of 35% to 60% by weight. In other words, the remaining proportion in the range of 65% to 40% by weight of the binder phase is formed by a metal binder material, which may contain Co and optionally other components according to the above. The sintered carbide material formed when the proportion of intermetallic phase material is in the range of 35% to 60% by weight allows the manufacture of soil excavation tools which are subject to high demands and are frequently subjected to strong impact-like loads. For example, in this case, the digging teeth of an excavation shovel, the tools of a crusher, the tools of a shredder, the tools of a mulcher, the tools of a milling machine, the tools of a drill may be equipped with one or more such sintered carbide materials.
[0026] The sintered carbide material according to the invention can also be characterized in that the proportion of intermetallic phase material in the binder phase is in the range of 40% to 50% by weight. In other words, the remaining proportion in the range of 60% to 50% by weight of the binder phase is formed by a metal binder material, which may contain Co and optionally other components according to the above. With the sintered carbide material formed when the proportion of intermetallic phase material is in the range of 40% to 50% by weight, high performance tools, such as cutting elements for soil excavation, in particular round shank chisels, drill bits for earth drills or agricultural soil excavation tools (ploughshares, cultivator tips, rotary harrow tips, etc.), can be manufactured. In this case, it is conceivable, for example, that the cutting tips of such round shank chisels are composed of a material body manufactured from the sintered carbide material according to the invention.
[0027] According to the invention it is possible to provide that the metallic binder material and / or the intermetallic phase material comprises Nb and / or Ti and / or Ta and / or Mo and / or V and / or Cr, advantageously one or more of these materials being present in dissolved form in the binder phase and / or in the form of carbides in the binder phase.
[0028] However, it is also conceivable that one or more of the aforementioned components are incorporated in at least some of the crystal lattices of the intermetallic phase material. For example, titanium atoms (or another material of the aforementioned group) occupy Al or W lattice sites in the crystal lattice of the intermetallic phase material and, like W, increase the precipitation temperature of the intermetallic phase material. Thus, on the one hand, the intermetallic phase material can be precipitated more effectively, since the initiation of precipitation already takes place at high temperatures, where the diffusion rate is significantly higher. Furthermore, this measure allows the sintering process to be adjusted to be stoichiometric with respect to the carbon proportion, since titanium (or another material as mentioned above) takes over the role of tungsten. On the other hand, this measure allows a significant increase in the hot strength of the sintered carbide material.
[0029] According to one variant of the invention, it can be provided that the carbon proportion is adjusted to be stoichiometric or even less than stoichiometric. This measure prevents or minimizes graphite precipitation in the sintered mass, which would be caused by a carbon proportion greater than stoichiometric. The inventors have recognized that such intercalation has a detrimental effect on the fracture strength of the sintered carbide material.
[0030] According to the invention, the carbon percentage in the cemented carbide material is C 化学量論量 (wt%) - 0.003 × binder content (wt%) to C 化学量論量 (wt%) - up to 0.012 x binder content (wt%) and advantageously in the range C 化学量論量 (wt%) - 0.005 × binder content (wt%) to C 化学量論量 (wt%) - up to 0.01 x binder content (wt%) It is particularly possible to provide for a range of
[0031] According to the invention, it is also possible to provide that the proportion of Mo and / or Nb and / or Ti and / or Ta and / or Cr and / or V in the binder phase is ≦15 at.%. The abovementioned elements in particular form carbides as a rule. Within the scope of the invention, it is now possible to provide that the material composition is selected such that these elements are dissolved in small amounts in the intermetallic binder phase depending on their solubility product and their affinity for carbon, so that they can be incorporated into the crystal lattice of the intermetallic phase material and / or that they can dissolve in the metallic binder phase. If a sintered carbide material with a high toughness of the binder phase is desired, it is desirable to limit the proportion of carbide forms to small amounts. In that case, it is desirable for the material to be present in a total proportion of ≦15 at.%.
[0032] Preferably, the coercive force H of the cemented carbide material cM It is possible to provide that: H cM[kA / m]>(1.5+0.04×B)+(12.5-0.5×B) / D+4[kA / m], Advantageously, H cM [kA / m]>(1.5+0.04×B)+(12.5-0.5×B) / D+6[kA / m], Particularly preferably, H cM [kA / m]>(1.5+0.04×B)+(12.5-0.5×B) / D+10[kA / m] where B is the percentage by weight of metallic binder phase material in the binder phase or the sum of metallic binder phase material and intermetallic phase material in the cemented carbide material (% by weight) and D is the grain size of the dispersed WC determined by the intercept method according to DIN ISO 4499, Part 2.
[0033] For typical hard alloys containing Co in the binder phase and no intermetallic phase material, the coercivity is usually used to indirectly determine the average grain size of WC at a given binder content. According to the present invention, the intermetallic phase material significantly increases the coercivity. Thus, the coercivity can be indirectly evaluated as an indicator of the strengthening of the binder phase by the intercalated intermetallic phase material. The higher the coercivity, the greater the sum of the interfaces between the metal binder material, the intermetallic phase material and WC. The greater the number of precipitated intermetallic phase materials, the better the support of the individual crystals of the intermetallic phase material to each other in the binder phase, especially at high temperatures (especially at high tool use temperatures).
[0034] Coercive force H of sintered carbide material CM [kA / m]>(1.5+0.04×B)+(12.5−0.5×B) / D+4[kA / m] can be used primarily for the above-mentioned wear protection applications, e.g. wear protection.
[0035] The coercivity of the sintered carbide material, preferably H CM [kA / m]>(1.5+0.04×B)+(12.5-0.5×B) / D+6[kA / m] can be used mainly for the above-mentioned earth excavation tools where high demands are imposed.
[0036] The coercivity of the sintered carbide material, preferably HCM [kA / m]>(1.5+0.04×B)+(12.5-0.5×B) / D+10[kA / m] can be mainly used for the high performance tools mentioned above.
[0037] According to one variant of the invention, it can also be provided that the coercivity of the cemented carbide material is 20% higher than the coercivity of a hard alloy body having the same composition and WC grain size as the cemented carbide material, in which the binding phase is formed exclusively from a metal binder, which does not contain intermetallic phase material.
[0038] Thus, a hard alloy body having the same composition is a hard alloy body comprising 70-95% by weight of dispersed tungsten carbide and a binder phase, the binder phase comprising a metallic binder material but no intermetallic phase material, the proportion of metallic binder material in the cemented carbide material being 5-30% by weight, the binder material otherwise having the same or nearly the same composition as the binder material of the cemented carbide material according to the invention.
[0039] For example, mention may be made in this context of a cemented carbide material according to the invention comprising tungsten carbide in dispersed form as hard material and a cobalt binder.
[0040] As mentioned above, the coercivity is an indirect indication of the content / proportion of intermetallic phase material in the binder phase, and therefore the degree of strengthening of the binder phase.
[0041] Within the scope of the present invention, the sintered carbide material may be configured such that the sintered carbide material has a hot compressive strength of ≥ 1650 MPa at a temperature of 800 ° C and a strain rate of 0.001 1 / s and / or such that the sintered carbide material has a hot compressive strength of ≥ 1600 MPa at a temperature of 800 ° C and a strain rate of 0.01 1 / s (measured on cylindrical test pieces with a diameter of 8 mm and a height of 12 mm). With a sintered carbide material in which the proportion of metal binder material in the binding phase is 5-7% by weight and the proportion of WC is in the range of 93-95% by weight, advantageously in which case WC is present in the form of coarse grains with an average grain size in the range of 2-5 μm, cutting tips, in particular for road cutting chisels, can be produced.
[0042] In the context of the present invention, the abovementioned advantageous effects are particularly pronounced in the case of coarse-grained hard alloys. In one preferred variant of the invention, it is therefore provided that the dispersed tungsten carbide is present in the cemented carbide material in the form of grains whose average grain size, measured according to DIN ISO 4499 Part 2, is in the range from 1 to 15 μm, advantageously in the range from 1.3 to 10 μm, particularly preferably in the range from 1.3 to 2.5 μm or in the range from 2.5 to 6 μm.
[0043] Advantageously, it is provided that the maximum proportion of Fe in the binding phase is 5% by weight and / or that other unavoidable impurities are present in the binder material.
[0044] If it is provided that the intermetallic phase (M,Y)3(Al,X) has the crystal structure L12 (space group 221) according to ICSD (Inorganic Crystal Structure Database), a microstructure of the binder phase results in which the crystals of the intermetallic phase are uniformly distributed in the metal binder material and can effectively support each other when the sintered carbide body is subjected to high loads.
[0045] Advantageously, and preferably for the application of earth-digging tools, it is provided that the intermetallic phase material has a maximum size of 1500 nm, advantageously of 1000 nm.
[0046] According to a preferred configuration variant of the invention, it can be provided that the cemented carbide material is free or as free as possible from eta phase and / or Al2O3. The inventors have realized that it is desirable for the maximum proportion of eta phase or the maximum proportion of Al2O3 to be at most 0.6% by volume relative to the total cemented carbide material. If both substances are present in the cemented carbide material, it is advantageous for the sum of eta phase material and Al2O3 to be at most 0.6% by volume.
[0047] The particle size of the Al2O3 and / or eta phase material is preferably at most 5 times the average particle size of WC, where the average particle size of WC and the particle size of the Al2O3 and / or eta phase material can be determined by the intercept method (in accordance with DIN ISO 4499 Part 2).
[0048] The toughness of cemented carbide materials can be adversely affected by the eta phase or by Al2O3. If the eta phase is present in a high proportion, cemented carbide materials are conditionally suitable for use in earth-digging tools where high demands are placed on them. The same is true for Al2O3.
[0049] As noted above, cemented carbide materials can be hard alloys that have a strengthening binder phase, the strengthening being achieved by precipitation of intermetallic phase material during cooling in the sintering process.
[0050] For the production of the hard alloy according to the invention, the nominal composition of the raw materials at the initial weighing may be selected as follows: 70-95 wt. % WC, 1-28 wt. % metallic binder and 1-28 wt. % intermetallic phase. The metallic binder may contain the element Co, and optionally Fe and / or other components. The intermetallic phase is Ni3Al at the initial weighing.
[0051] According to the invention, the cemented carbide material has a binder phase with the following chemical element composition: Ni>25wt%, Al>4wt%, balance Co and dissolved binder components such as W and / or C; Advantageously, Ni>35% by weight, Al>5% by weight, balance Co and dissolved binder components such as W and / or C; Particularly preferred is Ni>40 wt.%, Al>6.5 wt.%, balance Co and dissolved binder components such as W and / or C. In particular, it can be provided that the ratio of the weight percentage of Al to the weight percentage of Ni is >0.10.
[0052] According to a preferred variant of the invention, it can be provided that the proportion of oxygen in the binder phase is ≦2% by weight, advantageously ≦1.5% by weight. The inventors have realized that it is advantageous if no Al2O3 or only very small amounts of Al2O3 are present in the binder phase. This material reduces the ductility or toughness of the binder and the cemented carbide material becomes more brittle. Al2O3 thus weakens the binder phase and thus reduces the strength of the cemented carbide material. Minimizing the proportion of oxygen in the binder phase as proposed prevents or minimizes the formation of this substance.
[0053] The subject of the present invention is a cemented carbide material, in particular a hard alloy, which comprises 70-95% by weight, advantageously 80-95% by weight, of tungsten carbide in dispersed form and a binder phase, which comprises a metallic binder material and, at least in partial regions of the cemented carbide material, an intermetallic phase material, advantageously (M,X)3(AL,Y), where M=Ni, Y=Co and / or other components and X=tungsten and / or other components, and the binder phase has the following chemical element composition: Ni>25wt%, Al>4wt%, balance Co and dissolved binder components such as W and / or C; Advantageously, Ni>35% by weight, Al>5% by weight, balance Co and dissolved binder components such as W and / or C; Particularly preferred is Ni>40 wt.%, Al>6.5 wt.%, balance Co and dissolved binder components such as W and / or C. and in particular it is possible to provide a ratio of the weight percentage of Al to the weight percentage of Ni of >0.10.
[0054] Manufacturing (including explanation of measurement methods) Manufacturing: Below is described how cemented carbide materials containing intermetallic phase material in the binder phase can be produced by a powder metallurgy process routine, which is divided into the process steps of producing a compressible powder mixture, compacting and finally sintering to obtain a compact dense cemented carbide body.
[0055] As starting material for the production of the powder mixture, WC powders of various grain sizes can be used, in particular coarse-grained WC with a grain size FSSS>25 μm. The starting powders for the binder phase are ultrafine-grained cobalt powder (FSSS 1.3 μm) and nickel-aluminium powder, for example Ni-13Al powder with an aluminium content of about 13.3% by weight. The grain size of the Ni-Al powder is FSSS<70 μm, preferably FSSS<45 μm. To adjust and balance the targeted carbon content, W metal powder (FSSS<2 μm) and carbon black are used. For alloying the binder phase with alloying elements such as Ti, Ta, Mo, Nb, V, Cr, their carbide powders or W-containing mixed carbides with a grain size <3 μm are used.
[0056] The powder mixture is produced by wet grinding according to the prior art, preferably in a ball mill equipped with hard alloy balls. As grinding media, ethanol and hexane are used. Other possible grinding media would be acetone, or an aqueous medium containing suitable inhibitors.
[0057] For the production of powder mixtures of cemented carbide materials with binder contents >15%, a single grinding step is sufficient due to the high binder content and enhanced recrystallization, whereas for binder contents below 15%, a multi-stage wet grinding process is advantageous to effectively grind the Ni-Al powder and minimize oxide formation during the grinding process.
[0058] In the first step, the Ni-Al powder is intensively mixed with the grinding liquid and coarse-grained tungsten carbide with an average grain size FSSS>20μm, preferably 30-60μm. If necessary, pressing aids, small amounts of alloying components and cobalt powder can already be added here.
[0059] The grinding parameters (time, ratio of grinding balls to grinding material, grinding media) and the ratio of WC to Ni-Al powder vary depending on the WC grain size set in the cemented carbide material.
[0060] In the second step, 50 to 80% by weight of WC raw material of a specified particle size is added to this pre-ground material and mixed, with the main focus being on reducing agglomerates and obtaining as homogeneous a mixture as possible.
[0061] If alloy adjustment and addition of pressing aid have not already been carried out in the first grinding step (pre-grinding VM), this can also be carried out in the second step.
[0062] The slurry obtained from the wet milling is dried by conventional techniques and converted into a powder suitable for pressing, preferably by the spray drying process.
[0063] The forming is preferably carried out directly by axial pressing in a mechanical, hydraulic or electromechanical press.
[0064] Sintering is carried out in vacuum at 1350-1550° C., preferably in industrial sintering-HIP furnaces, in which an overpressure is generated after liquid phase sintering by introducing an inert gas, in which any residual porosity present can be eliminated. [Brief description of the drawings]
[0065] [Figure 1] FIG. 1 is a phase diagram of WC—Co—Ni3Al for 3 wt.% Co and 3 wt.% Ni3Al. [Diagram 2] FIG. 1 shows a cemented carbide material according to the invention in the form of a hard alloy. [Diagram 3] FIG. 1 shows a cemented carbide material according to the invention in the form of a hard alloy. [Figure 4] FIG. 1 is a diagram showing the hot compressive strength of a hard alloy containing 6% binder when the test temperature and strain rate are changed.
[0066] FIG. 1 shows an exemplary phase diagram of WC-Co-Ni3Al for 3 wt. % Co and 3 wt. % Ni3Al, which illustrates the formation of these precipitates.
[0067] After solidification of the melt, initially only WC and a solid solution of Co, Ni, Al, W and C are present. Only at about 950-600°C do intermetallic phase materials precipitate out of this solid solution, where the intermetallic phase materials are formed according to the structural formula (M,Y)3(Al,X), where M=Ni, Y=Co and / or other elements, and X=Tungsten and / or other elements. These intermetallic phase materials can be made visible with a scanning electron microscope.
[0068] In Figures 2 and 3 two different cemented carbide materials according to the invention in the form of hard alloys are shown by such scanning electron microscope images. The binder phase of such hard alloys can be clearly seen and the intermetallic phase material (light phase) 10 and the metallic binder material 30 (dark) can be distinguished. The WC grains 20 are bonded to each other via the binder phase.
[0069] It is found that the intermetallic phase material is uniformly distributed in the binder phase, with the crystals of the intermetallic phase material having a cubic shape and preferably smaller than 1500 nm. The crystals of the intermetallic phase material (M,Y)3(Al,X) have the crystal structure L12 (space group 221) according to ICSD (Inorganic Crystal Structure Database).
[0070] In order to allow easy precipitation of the intermetallic phase material in the binder phase, it can be advantageously provided that the (M,Y)3(Al,X) content in the binder phase is 40% or more, with the carbon proportion being adjusted to be stoichiometric or less than stoichiometric.
[0071] It was found that the higher the tungsten dissolution in the binder phase, the more stable the precipitation of the intermetallic phase was, because the precipitation range shifted to higher temperatures as "Co3W" was incorporated into the crystal structure of the intermetallic phase material.
[0072] Here the elements Mo, Nb, Cr, V and especially Ti, Ta show a similar effect and can be added to the alloy in small amounts (<15 at % in the binder).
[0073] The amount of alloy that can be used depends on the solubility product of each of the metal carbides. Even if its magnitude is negligible, a surprisingly clear effect has been shown that is not due to a grain refinement effect.
[0074] Based on the improved stability and precipitation behavior, the addition of other elements to the alloy allows the percentage of intermetallic phase material in the binder to be reduced, even below 40%. Furthermore, in the presence of, for example, Ti and Ta, these elements take over the role of tungsten as a stabilizer, making it unnecessary to adjust the carbon percentage below the stoichiometric amount.
[0075] The effect of the precipitation of intermetallic phase materials on hot strength can be impressively demonstrated by hot compression tests. Figure 4 shows the hot compression strength of a hard alloy containing 6% binder at different test temperatures and strain rates. Especially at the test temperature of 800°C, the strength increases by about 40-50% due to the intermetallic phase materials.
[0076] Physical property values are measured on sintered samples of cemented carbide materials and serve to characterize the material and its properties.
[0077] In the case of hard alloys, the coercive force H cM Measurement of the specific saturation magnetization of 4 ps has been established as a non-destructive testing method.
[0078] Both measurement parameters are also determined for the characterization of the cemented carbide material according to the invention with Förster Koerzimat® 1.097.
[0079] Another parameter for the characterization of materials is density, which is determined by weighing according to Archimedes' principle.
[0080] The hardness of the blanks is determined on metallographically prepared polished specimens of hard alloys in accordance with valid standards, advantageously using the Vickers HV10 hardness test with a test load of 10 kp (ISO 3878).
[0081] Similarly, the porosity (DIN-ISO 4499-4 standard) and aluminium oxide particles of the sintered material are checked and evaluated by optical microscopy on the polished samples. Comparative images of A or B porosity can be used to estimate the volume percentage of aluminium oxide in the microstructure, where A08 or B08 corresponds to a volume percentage of approximately 0.6 volume %. For optical microscopy examination of the eta phase, this is etched with Murakami's reagent according to the standard (DIN-ISO 4499-4). The average grain size of the WC is determined according to DIN ISO 4499-2. In this case, SEM (scanning electron microscope) images are evaluated by sectioning.
[0082] The proportion of intermetallic phases in the binder and the maximum size of the precipitated particles are also determined by SEM images, but using an in-lens BSE detector. For this purpose, images are taken at several points of the sample and an evaluation is carried out on representative cross sections by image processing and determination of the area proportion by gray scale division.
[0083] Working Example: The following table shows examples of sintered carbonized bodies according to the invention, which in principle can be produced by the same methods as described above: [Table 1]
[0084] [Table 2-1] [Table 2-2] [Table 2-3]
Claims
1. % by weight, preferably 80 to 95% by weight, of tungsten carbide in dispersed form and a binder phase, the binder phase includes a metallic binder material and, at least in a portion of the cemented carbide material, an intermetallic phase material; the proportion of said metal binder material in said cemented carbide material is between 1 and 28% by weight, preferably between 1 and 19% by weight; the proportion of said intermetallic phase material in said cemented carbide material is between 1 and 28% by weight, preferably between 1.5 and 19% by weight; The metallic binder material comprises Co; The intermetallic phase material has the structural formula (M, Y): 3 A cemented carbide material formed according to (Al,X), where M=Ni, Y=Co and / or other elements, and X=Tungsten and / or other elements.
2. The cemented carbide material of claim 1 , wherein the binder phase comprises two or more intermetallic phase materials or comprises only a single intermetallic phase material.
3. 3. The cemented carbide material according to claim 1 or 2, wherein the proportion of the intermetallic phase material in the binder phase is in the range of 25% to 70% by weight, preferably in the range of 30% to 70% by weight, more preferably in the range of 35% to 60% by weight, particularly preferably in the range of 40% to 50% by weight.
4. (M,X) in the bonded phase 3 3. The cemented carbide material according to claim 1, wherein the proportion of (AL,Y) is ≧30% by weight, preferably ≧35% by weight, particularly preferably ≧40% by weight.
5. 3. Sintered carbide material according to claim 1 or 2, wherein the metallic binder material and / or the intermetallic phase material comprises Nb and / or Ti and / or Ta and / or Mo and / or V and / or Cr, advantageously one or more of said materials being present in the binder phase in dissolved form and / or in the form of carbides.
6. 3. The sintered carbide material according to claim 1, wherein the carbon content in the sintered carbide material is adjusted to be stoichiometric.
7. The carbon percentage in the cemented carbide material is C 化学量論量 (wt%)-0.003 x binder content (wt%) to C 化学量論量 (wt%) - 0.012 x binder content (wt%) and advantageously in the range C 化学量論量 (wt%)-0.005 x binder content (wt%) to C 化学量論量 (wt%) - up to 0.01 x binder content (wt%) 7. The cemented carbide material of claim 6, wherein the modulus is in the range of
8. 3. The cemented carbide material according to claim 1 or 2, wherein the proportion of Mo and / or Nb and / or Ti and / or Ta and / or Cr and / or V in the binder phase is ≦15 at.%.
9. The coercive force H of the cemented carbide material cM but, H cM [kA / m]>(1.5+0.04×B)+(12.5-0.5×B) / ++[[kA / m]、 Advantageously, H cM [kA / m]>(1.5+0.04×B)+(12.5-0.5×B) / D+6[kA / m], Particularly preferably, H cM [kA / m]>(1.5+0.04×B)+(12.5-0.5×B) / D+10[kA / m] 3. The cemented carbide material according to claim 1 or 2, wherein B is the proportion of the binder phase in the cemented carbide material in % by weight and D is the grain size in μm of the dispersed WC determined by the intercept method according to DIN ISO 4499, Part 2.
10. 3. The sintered carbide material according to claim 1 or 2, wherein the hot strength of the sintered carbide material at a temperature of 800°C and a strain rate of 0.001 [1 / s] is ≧1650 [MPa], and / or the hot strength of the sintered carbide material at a temperature of 800°C and a strain rate of 0.01 [1 / s] is ≧1600 [MPa].
11. 3. The cemented carbide material according to claim 1, wherein the dispersed tungsten carbide is present in the cemented carbide material in the form of grains whose average grain size, measured in accordance with DIN ISO 4499 Part 2, is in the range from 1 to 15 μm, preferably in the range from 1.3 to 10 μm, particularly preferably in the range from 1.3 to 2.5 μm or in the range from 2.5 to 6 μm.
12. 3. Cemented carbide material according to claim 1 or 2, characterized in that the maximum proportion of Fe in the binder material is <5 wt.-% and / or other unavoidable impurities are present in the binder material.
13. The intermetallic compound phase material (M, Y) 3 The (Al,X) crystal has the crystal structure L1 according to ICSD (Inorganic Crystal Structure Database). 2 3. The cemented carbide material of claim 1 or 2, having space group 221.
14. 3. The cemented carbide material according to claim 1 or 2, wherein the intermetallic phase material has a maximum size (measured by sectioning on microscopic specimens) of 1500 nm, preferably 1000 nm.
15. Maximum proportion of eta phase or Al 2 O 3 or the maximum proportion of Al is at most 0.6 volume percent relative to the total cemented carbide material, or the eta phase material and Al 2 O 3 3. The cemented carbide material according to claim 1, wherein the sum of is at most 0.6% by volume.
16. A 2 O 3 3. The cemented carbide material of claim 1 or 2, wherein the average grain size of the eta phase material is at most 5 times the average grain size of the WC.
17. The binder phase has the following chemical element composition: Ni>25 wt.%, Al>4 wt.%, balance Co and dissolved binder components such as W and / or C; Advantageously, Ni>35% by weight, Al>5% by weight, balance Co and dissolved binder components such as W and / or C; Particularly preferred is a composition containing Ni>40 wt.%, Al>6.5 wt.%, the remainder Co and dissolved binder components such as W and / or C.
3. The cemented carbide material according to claim 1 or 2, wherein it is possible to provide in particular that the ratio of the weight percentage of Al to the weight percentage of Ni is >0.
10.
18. 3. The cemented carbide material according to claim 1, wherein the proportion of oxygen in the binder phase is ≦2% by weight, preferably ≦1.5% by weight.
19. A cemented carbide material, in particular a hard alloy, comprising 70-95% by weight, preferably 80-95% by weight, of tungsten carbide in dispersed form and a binder phase, which comprises a metallic binder material and, at least in partial regions of the cemented carbide material, an intermetallic phase material, preferably (M, X) 3 (AL,Y) where M=Ni, Y=Co and / or other elements, and X=tungsten and / or other elements; The binder phase has the following chemical element composition: Ni>25 wt.%, Al>4 wt.%, balance Co and dissolved binder components such as W and / or C; Advantageously, Ni>35% by weight, Al>5% by weight, balance Co and dissolved binder components such as W and / or C; Particularly preferred is a composition containing Ni>40 wt.%, Al>6.5 wt.%, the remainder Co and dissolved binder components such as W and / or C. In particular, it is possible to provide a cemented carbide material having a ratio of the weight percentage of Al to the weight percentage of Ni of >0.
10.
20. The sintered carbide material of claim 19, having the characteristics of claim 1 or 2.
21. At least half of the dispersed tungsten carbide is formed in the form of crystals that are not completely sintered, the grains having a non-prismatic shape, and / or 20. The cemented carbide material according to claim 1 or 19, wherein at most half of the dispersed tungsten carbide is formed in the form of sintered crystals, the grains of which have a prismatic shape.
22. 20. An earth excavation tool, in particular an earth excavator, in particular a road construction machine or an agricultural earth excavator, in particular a road mill, stabilizer or the like, which comprises a tool body, in particular made of steel, on which a sintered carbide material according to claim 1 or 19 is held in a fixed manner, in particular by a material connection, for example soldered or glued.